Organización contable a la empresa del Sr. Franklin Antonio Macas Leon de la ciudad de Loja, período octubre – diciembre de 2022 - Merino Chamba, Sheilly Dayanna (2023)
The Curricular Integration Work had the purpose of organizing accounting, as well as disclosing the economic and financial situation of the company under study, fulfilling the general objective. The methodology used was based on a qualitative-quantitative approach, with a mixed, exploratory-descriptive approach, and non-correlational design. Inductive, deductive, analytical, synthetic methods, and mathematical procedures were used, in addition to the use of the technological tool called Excel. To meet the specific objectives, it was necessary to develop an account plan and manual, which allowed for the organization of the main accounts involved in the economic activities of the entity. Furthermore, for the development of the second objective, main and auxiliary formats for the accounting process were designed according to the company's resources and operations. Among the main auxiliary books are: Diesel auxiliaries, in which diesel acquisitions were recorded on a weekly basis. Subsequently, accounts receivable and accounts payable auxiliaries were presented, which allow for knowing the state of outstanding receivables and payables. Finally, sales auxiliaries were presented, in which sales and service provision were recorded on a weekly basis. Subsequently, the accounting process was carried out, concluding with the presentation of Financial Statements, where timely and reliable data were reflected. At the end of the accounting process, a net profit of $91,630.15 was obtained; assets of $1,747,325.61; liabilities of $507,295.72, and equity of $1,240,029.89; significant information for its owner, based on which they can make appropriate decisions for the economic growth of the company.